Combined low-current discharge in copper vapor laser; Atomic and molecular pulsed lasers - Fedorov V. F. Valery Fedorovich; Shiyanov D. V. Dmitry Valeryevich; Fedorov K. V. Kirill Valerjevich; Evtushenko G. S. Gennady Sergeevich (2015, 2015)
В фонде НТБ ТПУ отсутствует